Good customer relationships - Olsson, Christel; Lekselius, Tove (Qualitative and Quantitative Methods in Libraries, 2019)
Objective: The objective of this study has been to improve the quality for the library users as well as the library staff. Background and questions: The background was the changes in questions in an Academic Library noticed by the library staff and the increase of ”nontraditional library questions”. How does this affect the library staff? Is the staff in need of other skills or competences? Does it affect the customer relationships? A number of questions were raised e.g. What is good customer services/relationships? How do we make sure that our library has it? Exactly what kind of questions are being asked at the library? Methods and Results: Using both qualitative and quantitative methods, we have worked very actively with our customer relations/customer services over the last years. The qualitative methods includes Quality Walk, Staff Diary, Critical Friend Evaluation among others. The quantitative method comprised of measuring/pinning down every single question asked at the library between September 2014 and September 2016 and then categorize and evaluate the findings. With this unique collection of data we have been able to improve our services further. From our findings we were able to compile new Documents and Guidelines for the library staff, regarding how we treat and meet our customers - a united and well informed staff contributes to good customer services. From 2014 until today we have seen different effects of our work, one example is that our National Satisfaction index went up to over 90% during this work. Conclusion and Summary: By raising the question of customer relationships and finding out exactly what kind of questions were being asked, we were able to contribute to increased awareness of the staff, improving the quality both for the library users and the library staff. The library is nothing without its users/customers, hence constantly working with customer relationships and keeping the question alive is crucial for as well customer relations as workplace satisfaction.